Recommendations for assessing earthworm populations in Brazilian ecosystems - Nadolny, Herlon; Santos, Alessandra; Demetrio, Wilian; Ferreira, Talita; Maia, Liliane dos Santos; Conrado, Ana Caroline; Bartz, Marie; Garrastazu, Marilice; Silva, Elodie da; Lavelle, Patrick; et al. (Pesquisa Agropecuaria Brasileira, 2020)
Earthworms are often related to fertile soils and are also frequently used as environmental quality indicators. However, to optimize their use as bioindicators, earthworm populations must be evaluated together with the environmental and anthropogenic variables regulating their communities. This review sought to identify the earthworm-sampling, soil chemical and physical, and environmental and anthropogenic attributes evaluated in 124 published studies that quantified earthworm abundance (>7,300 samples) in 765 sites with different types of climate, soils, land use, and management systems in Brazil. Soil chemical and physical attributes (except pH) were less reported (≤50% of studies) than other environmental variables such as sampling date, altitude, temperature, precipitation, climate and soil type, and land use (>50% of studies). Earthworms were rarely identified (24%) and few studies (31%) measured their biomass, although most provided adequate information on sampling protocol. Based on their importance in regulating earthworm populations, a set of variables is proposed to be evaluated when studying earthworm communities and other macrofauna groups. This should help guide future studies on earthworms in Brazil and other countries, optimize data collection and replicability, allow comparisons between different studies, and promote the use of earthworms as soil quality bioindicators.